Evaluation of corrosion resistance properties of N, N'-Dimethyl ethanolamine corrosion inhibitor in saturated Ca(OH)2 solution with different concentrations of chloride ions by electrochemical experiments - Ryu, H.-S.; Singh, J.; Yang, H.-M.; Lee, H.-S.; Ismail, Mohamed (ELSEVIER, 2016)
Steel rebars attain passivity in concrete environment. Passive film can be destroyed by acidification through carbonation and chloride ions from NaCl in concrete. There are different techniques have been employed to mitigate the corrosion problem of steel rebars embedded in concrete. Among different methods inhibitors are very popular and frequently used. Commercially available N, N′-Dimethyl ethanol amine (DMEA) inhibitor is studied in different concentrations of NaCl in saturated Ca(OH)2 solution. The performance of inhibitor was evaluated by potential time, electrochemical impedance spectroscopy and potentiodynamic techniques. DMEA inhibitor is showing 63–74% efficiency and effectively reduces the corrosion rate.